Kajian Literatur Inovasi Media Pembelajaran 3D Berbasis Website pada Pembelajaran IPAS Sekolah Dasar - Swastika Yasa, I Kadek Adi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid advancement of information technology has brought substantial changes to the field of education, particularly in the ways teachers deliver instruction and how students acquire knowledge. One emerging innovation that aligns with the demands of 21st-century learning is the integration of web-based 3D learning media. This study aims to examine the potential, strengths, and challenges of implementing 3D web-based instructional media to support thematic learning in elementary schools, specifically within the theme My Beloved Earth, My Suffering Earth. This research employs a literature review approach by analyzing various national and international sources related to digital media development, 3D technology, and thematic learning. The findings show that 3D learning media can enhance students’ interactivity, motivation, and conceptual understanding of environmental and earth science topics. Three-dimensional visualization enables students to explore natural phenomena in a more realistic and contextual manner. Additionally, integrating 3D media with website technology makes learning tools easier to access, more efficient, and compatible with a wide range of digital devices. Nevertheless, several challenges persist, including limited technological infrastructure, low digital literacy among some teachers, and the need for professional development in creating interactive media. Therefore, collaboration between teachers, media developers, and educational institutions is essential to optimize the implementation of this technology. Overall, web-based 3D instructional media hold strong potential as a strategic innovation in the digital transformation of elementary education, fostering active, creative learning and supporting the development of essential 21st-century competencies.